2010
DOI: 10.1007/s12072-010-9217-z
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of outcome in acute-on-chronic liver failure in children

Abstract: Background and aims Acute-on-chronic liver failure (ACLF) is associated with a high mortality rate in the absence of liver transplantation. There is limited data on predictors of survival in ACLF in children. Therefore, we prospectively studied the predictors of outcome of ACLF in children. Methods A prospective evaluation of 31 children in the age group of 1-16 years who fulfilled the criteria for ACLF according to Asian Pacific Association for the Study of the Liver (APASL) 2008 consensus was done. All conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
62
4
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(74 citation statements)
references
References 10 publications
7
62
4
1
Order By: Relevance
“…Complications such as bacterial or fungal infection, hepatic encephalopathy, HRS and electrolyte disturbance were also associated with poor prognosis. The results of the present investigation are concordant with those of Lal et al (15), who reported that high INR was an independent ACLF prognostic factor. Cellular immunity is impaired in patients with ACLF, increasing the risk of infection and the infection-associated mortality rate (16).…”
Section: Discussionsupporting
confidence: 93%
“…Complications such as bacterial or fungal infection, hepatic encephalopathy, HRS and electrolyte disturbance were also associated with poor prognosis. The results of the present investigation are concordant with those of Lal et al (15), who reported that high INR was an independent ACLF prognostic factor. Cellular immunity is impaired in patients with ACLF, increasing the risk of infection and the infection-associated mortality rate (16).…”
Section: Discussionsupporting
confidence: 93%
“…3Receiver operating characteristic curve of Acute Physiology and Chronic Health Evaluation (APACHE) II score the prognosis is determined by the degree of other organ system dysfunction and not by the severity of liver failure. Our findings are similar to those of other studies[1,2,4,[22][23][24][25][26][27][28][29][30].…”
supporting
confidence: 93%
“…A higher mortality of 50% is reported from adult data [2] as against the 39.3% of the pediatric cases having poor outcomes in the present study. The reported mortality of pediatric ACLF at two tertiary non-transplant Indian centres has been variable, ranging from 19.4% [9] to 59% [8]. The lower mortality of 19.4% [9] can be explained by exclusion of the more sick children from the cohort on account of referrals to the transplant centres.…”
Section: Resultsmentioning
confidence: 99%